The Role of Social Support Between Work-To-Life Conflict and Job Stress Among Nurses at Public Hospital - Azman, Famizah Asyikin; Arif, Lily Suriani Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to examine the relationship between work-to-life conflict and job stress as well as the role of social support as a moderator at Hospital Enche’ Besar Hajjah Kalsom, Kluang Johor. The objective of this study are to identify the level of work-to-life conflict and job stress. In addition, the objective of this study are also to study relationship between work-to-life conflict and job stress and to determine whether social support moderate the relationship between work-to-life conflict and job stress among the nurses at Hospital Enche’ Besar Hajjah Kalsom, Kluang, Johor. This study used data collection method by using questionnaires and simple random sampling. A total of 191 set of questionnaires received were analysed. The findings are presented in the form of percentage and mean, the analysis of correlation and hierarchical multiple regression. The study found that nurses in the hospital experience the moderate level of work-to-life conflict and job stress. The findings also found that there is significant relationship between work-to-life conflict and job stress. Furthermore, the results show that social support was unable to moderate the relationship between work-to-life conflict and job stress among the nurses. At the end of the study, several improvement proposals submitted to reduce work-to-life conflict and job stress among the nurses as well as making recommendations for future studies